Hyperechogenicity of the substantia nigra in Parkinson's disease - Ressner, Pavel; Skoloudík, David; Hlustík, Petr; Kanovský, Petr (Journal of neuroimaging, 2007)
Substantia nigra (SN) was assessed by transcranial sonography (TCS) in 47 Parkinson's disease (PD) patients and in 39 healthy volunteers. A semiquantitative echogenicity scale was created with arbitrary values ranging from 1 to 5, zones with grade >or=3 and larger than 0.19 cm(2) were recorded as hyperechogenic SN. TCS examination of SN as a diagnostic test for PD in our study showed 87.2% sensitivity and 94.9% specificity.
Keywords: Chi-Square Distribution; Humans; lidé středního věku; Ultrasonography, Doppler, Transcranial; Female; Aged; dospělí; senioři; lidé; Substantia Nigra; rozdělení chí kvadrát; Adult; ženské pohlaví; Male; Middle Aged; substantia nigra; Aged, 80 and over; senioři nad 80 let; mužské pohlaví; Parkinson Disease; ultrasonografie dopplerovská transkraniální; Parkinsonova nemoc